2021
DOI: 10.1186/s12912-021-00573-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of self-re-learning using video recordings of advanced life support on nursing students’ knowledge, self-efficacy, and skills performance

Abstract: Background Nurses are presumably the first to see an in-hospital cardiac arrest patient. This study proposed measuring nursing students’ knowledge, self-efficacy, and skills performance in advanced life support (ALS), 6 months after training, by sending videos taken during their final skills test after the ALS training. Methods This is an experimental study using a randomised control group design. This study was conducted from June to December 2018… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
(37 reference statements)
0
6
0
6
Order By: Relevance
“…En el contexto educativo, incluido el de la salud, la recuperación de la información almacenada en la memoria es importante para la retención de conocimiento a largo plazo y la transferencia de contenidos a nuevas situaciones 21 . Los hallazgos de la presente investigación demuestran que, aunque el 30,2% de los profesionales mencionó que había participado en entrenamiento de soporte vital avanzado antes de la recolección de datos, no presentaron mejores respuestas teóricas ni mayor retención del conocimiento aprendido después de tres meses de la experiencia simulada.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En el contexto educativo, incluido el de la salud, la recuperación de la información almacenada en la memoria es importante para la retención de conocimiento a largo plazo y la transferencia de contenidos a nuevas situaciones 21 . Los hallazgos de la presente investigación demuestran que, aunque el 30,2% de los profesionales mencionó que había participado en entrenamiento de soporte vital avanzado antes de la recolección de datos, no presentaron mejores respuestas teóricas ni mayor retención del conocimiento aprendido después de tres meses de la experiencia simulada.…”
Section: Discussionunclassified
“…Por lo tanto, los enfermeros que reciben periódicamente capacitación simulada tienen más probabilidades de mantener los conocimiento y habilidades aprendidas a largo plazo en proporción al intervalo de actualización, es decir, cuanto menor sea el tiempo entre cada capacitación, menor será la curva de olvido y mayor la retención 10 . Sin embargo, los intervalos entre capacitaciones y/o entrenamientos que involucren actividades simuladas también deben tener en cuenta las características de los participantes, tales como el tiempo de experiencia profesional y el conocimiento teórico y práctico sobre el tema estudiado 21 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Besides, some researchers are inclined to study English learners' self-efficacy connected with learning methods, learning motivation and learning strategies. For example, one recent research conducted by Jang Kyeongmin, who mainly studied effectiveness of self-re-learning using video recordings, showed that self-study with videos taken during an ALS skills test helps enhance the sustainable effects of training such as knowledge, self-efficacy, and skills performance (Jang, 2021). Another scholar, Se Hyun Kim, who worked hard in the field of Second Language Learners' Self-efficacy and English Achievement, claimed that adolescents with higher self-efficacy reported more integrative motivation, and greater integrative motivation was associated with higher English achievement .…”
Section: Related Literature On the Correlation Analysis Of Learners' Self-efficacymentioning
confidence: 99%
“…Research on video-based learning tools for nurses describes the development process mostly as a summarized part of the observational or experimental findings. [29,30] Studies that more thoroughly describe the development process are mainly focused on the acute nursing care settings such as stroke care, cardiac care, and pulmonary care scenarios. [31,32] Research on the development process of video-based learning tools for chronic geriatric nursing care is limited.…”
Section: Introductionmentioning
confidence: 99%